ANALISIS DATA CURAH HUJAN SEBAGAI PENYEBAB BANJIR DI GEDONGTATAAN, LAMPUNG - Anna Mariana (Inovasi Pembangunan : Jurnal Kelitbangan, 2022)
Flood occurs almost every year in Gedongtataan which inundation depth can reach 1.5 meters and submerges some villages in Gedongtataan. The flood causes negative effects such as health problems, road congestion, and material damage. The flood that has been occured was caused by high rainfall. The study had objective to analyze rainfall as a factor causing floods in Gedongtataan. The study used simple analysis for the rainfall pattern and Gumbel method to analyze the frequency of maximum rainfall. The study resulted in that high rainfall occured in January, February, and December. The maximum daily rainfall in Gedongtataan reached 118 mm/day and maximum daily rainfall can be 155 mm/day for 100 years return period from Gumbel method. The high rainfall intensity and also lack capacity of drainages and inability of other flood control in flowing runoff has caused flood in Gedongtataan.